Unraveling Triadic Relationship in Trump’s Foreign Policy: Internationalism, Nationalism, and Trumpism - Suporn, Thapiporn (Thai Journal of East Asian Studies, 2019)
This article provides a new framework for analyzing the dynamics of U.S. foreign policy establishment in the Trump administration. Since Trump became the President of the United States in 2017, the foreign policy establishment has changed drastically to the point that it now consists of three ideologies: internationalism, nationalism, and Trumpism. Though the three ideologies may contradict, they coexist and, above all, take the helm of American foreign policy. The nature of competing yet coexisting three ideologies is defined as “triadic relationship”. This article argues that internationalism and nationalism are sometimes eclipsed by Trumpism, but they are not be completely silenced once overshadowed by Trumpism. Rather, when Trumpism reaches its goals, it will “juggle back” enabling nationalism and internationalism to resume their duties. Moreover, the distinctions between internationalism, internationalism, and Trumpism are not clearly drawn in the sense that internationalism and Trumpism can only be associated with security issues whereas nationalism is connected to economic ones. Instead, any ideology can compete in the security or economic realm, and briefly dominates U.S. foreign policy in a "juggling back and forth" way. In conclusion, the triadic relationship, along with the concept of juggling back and forth, can clarify the complexities of President Trump’s foreign policy and the dynamics inside the foreign policy establishment.